Effects of Metabolites Derived From Gut Microbiota and Hosts on Pathogens - Li, Zhendong; Quan, Guomei; Jiang, Xinyi; Yang, Yang; Ding, Xueyan; Zhang, Dong; Wang, Xiuqing; Hardwidge, Philip R.; Ren, Wenkai; Zhu, Guoqiang (Frontiers in Cellular and Infection Microbiology, 2018)
Intestinal metabolites participate in various physiological processes, including energy metabolism, cell-to-cell communication, and host immunity. These metabolites mainly originate from the gut microbiota and hosts. Although the number of host metabolites is dominant in intestines, such as free fatty acids, amino acids and vitamins, the metabolites derived from gut microbiota are also essential for intestinal homeostasis. In addition, some metabolites only generated and released by gut microbiota, such as bacteriocins, short-chain fatty acids, and quorum sensing autoinducers. In this review, we summarize recent studies regarding the crosstalk between pathogens and metabolites from different sources, including influence bacterial development and activate/inhibit immune responses of host. All of these functions would affect the colonization and infection of pathogens. This review provides clear ideas and directions for further exploring the regulatory mechanisms and effects of metabolites on pathogens.